MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MULTIMEDIA PADA MATA PELAJARAN PAI KELAS VII DI SMPN 1 DOLOK BATU NANGGAR - Muharina Eliani Yuwasita (Universitas Islam Negeri Sumatera Utara Medan, 2022)
The purpose of this Classroom Action Research is to find out whether there is an increase in student learning outcomes in Islamic Religious Education subjects through the use of multimedia. The research was carried out in class VII . The object of this research is students, totaling 32 students. This research is a Classroom Action Research (CAR) which consists of two cycles. Based on the results of research, the use of interactive multimedia can improve student learning outcomes in PAI subjects. This is evidenced by an increase in the percentage of student learning outcomes in PAI subjects in each cycle, namely: (1) In the first cycle, the percentage of student learning outcomes who complete reaches 59.3% while those who do not complete are 40.7%.( 2) In cycle II, the percentage of student learning outcomes who complete reaches 87.5% while those who do not complete 12.5%. Thus, it can be concluded that the use of multimedia can improve student learning outcomes in Islamic Religious Education subjects in class VII. The results of this study can be used as input for educators and prospective educators to improve skills in using media, especially interactive multimedia in improving learning outcomes so as to create ideal learning quality with good standards.